INSTRUCTIONAL MANAGEMENT OF ESP FOR AGROTECHNOLOGY AND AGRIBUSINESS STUDIES: AN EXPERIENTIAL REFLECTIVE PRACTICE - Supriyono Supriyono (Center of Language and Cultural Studies [CLCS], 2016)
This paper discusses reflection of ESP class instructional management for Agro Technology and Agribusiness studies at the Faculty of Agriculture, Balitar Islamic University. The instructional management comprises analysis of students’ needs, competence and behavior, instructional preparation, instructional intervention using a combined pedagogical and instructional leadership approach, and instructional evaluation. This research was a reflective approach towards instructional practices. The study found out that instructional processes, the combined students centered task-based approach of language teaching and situational leadership approach, have resulted excellent achievement. Students successfully translated English texts to acceptable Indonesian conversion and worked out for producing final paper work of scientific articles and books transliteration. The combination of pedagogical and leadership approach in instructional management has satisfied the aims of ESP teaching for the Agro Technology and Agribusiness studies.